Follow-up of bowel endometriosis resections performed using the double circular stapler technique: A decade's experience. - Claudio Peixoto Crispi; Claudio Peixoto Crispi; Claudia Maria Vale Joaquim; Paulo Sergio da Silva Reis; Nilton de Nadai Filho; Bruna Rafaela Santos de Oliveira; Camilla Gabriely Souza Guerra; Marlon de Freitas Fonseca (PLoS ONE)
Study objective To report individual early and long-term functional outcomes of 43 women who underwent double circular stapler technique (DCST) for colorectal deep endometriosis (DE). Methods This multidisciplinary observational study was a retrospective case series report exploiting a long-established database of clinical information from a single private institution. The cohort consists of consecutive patients from January/2010 through July/2021 who underwent minimally invasive surgical treatment of DE. Inclusion criteria: all women whose bowel DE was managed by DCST. The assessment of bowel function was based on Obstructed Defecation Syndrome score, Gastrointestinal Symptom Rating Scale and Bowel Function in the Community Tool. Outcomes also included intra and postoperative complications, lower urinary tract symptoms, endometriosis-related menstrual and nonmenstrual pain (numeric rating scale), and conception. The analysis of the results was guided by a semi-qualitative reasoning based on individual changes. Results The follow-up ranged from 1.4 to 123.8 months (median 38.2). All women presented with DE (mostly rASRM stage 4) and underwent large resections. No procedure was converted to open surgery nor required blood transfusion or ostomies. There was no anastomotic leakage. The risk of rectovaginal bowel fistula was 2.3% (CI 95%: <0.1-7.0) - one case. No patient had long-term urinary retention after surgery. At the most recent follow-up on dysuria, dyschezia, dysmenorrhea, dyspareunia and cyclic low back pain, 88 to 100% of women had favorable responses (improvements ≥ 3 points in symptomatic women or asymptomatic women who remained pain-free). One patient reported important worsening of her intestinal function, requiring continuous use of laxatives. Considering the 20 women with pregnancy intent, 14 (70%) conceived after surgery. Discussion / conclusion Preliminary results were encouraging in the past. The current assessment including long-term follow-up supports DCST for colorectal DE as a feasible, useful, and safe strategy for avoiding segmental colorectal resection when appropriately indicated and properly performed.